أثر تبني معيار الإبلاغ المالي الدولي - معلى حنان (University Of Eloued جامعة الوادي, 2024)
تسعى هذه الدراسة بشكل أساسي إلى تحديد الآثار المحتملة لتبني متطلبات المعيار الدولي للإبلاغ المالي IFRS16 المتعلق بعقود الإيجار على القوائم المالية المعدة وفق النظام المحاسبي المالي SCF في البيئة الجزائرية، والوقوف على مدى قدرة المؤسسات الاقتصادية الجزائرية على تطبيق هذه المتطلبات، ولتحقيق هذه الأهداف و اختبار صحة فرضيات هذه الدراسة تم الاعتماد على المنهج الوصفي التحليلي، وتم استخدام أداة الاستبيان وتوزيعها على عينة مكونة من ممارسي مهنة المحاسبة في الجزائر بالإضافة إلى الأساتذة الجامعيين المتخصصين في مجال المحاسبة، حيث تم توزيع 190 استمارة استبيان على مفردات عينة الدراسة في مختلف ولايات الوطن، واسترجاع 136 استمارة صالحة للتحليل والتي تمت معالجتها إحصائيا باستخدام برنامج (SPSS V25). وتوصلت هذه الدراسة إلى أن التوجه إلى تبني متطلبات معيارIFRS16 المتمثلة في متطلبات إثبات عقود الإيجار، ومتطلبات قياسها، ومتطلبات عرضها والإفصاح عنها في القوائم المالية، في البيئة الجزائرية سيكون لها تأثير جوهري على محتوى القوائم المالية وجودة المعلومة المحاسبية وكذا مختلف القرارات التي يتخذها مستخدمي القوائم المالية ويرتبط هذا التأثير بمدى قدرة المؤسسات الاقتصادية الجزائرية على التحكم والالتزام بتطبيق متطلبات معيارIFRS16 المتعلق بعقود الإيجار. وأوصت هذه الدراسة على ضرورة تحيين قواعد النظام المحاسبي المالي SCF وإجراء التعديلات اللازمة على التشريع الجبائي بما يتماشى مع متطلبات معيارIFRS16، وتوفير البيئة الملائمة التي تسمح بتطبيق هذه المتطلبات بشكل جيد من طرف المؤسسات الاقتصادية الجزائرية. Abstract: This study chiefly seeks to determine the potential effects of adopting the new requirements of the International Financial Reporting Standard IFRS16 related to lease contracts on the financial statements prepared according to the financial accounting system SCF in the Algerian environment as well as to determine the extent to which Algerian economic institutions are capable to apply these requirements. Consequently, this research inquiry was operated under the analytical descriptive approach in order to achieve the main objectives and to test the validity of the formulated hypotheses at the outset of the study. Methodologically, one data gathering instrument was employed in this study which is respectively, the questionnaire that was distributed to a sample consisting of practitioners of the accounting profession in Algeria, in addition to university professors specialized in the field of accounting. In essence, a total of 190 questionnaires were distributed to the study sample in various cities nationwide, and only 136 valid questionnaires were retrieved for analysis. The later were processed statistically using the (SPSS V25) program. This study concluded that the adaptation of the new requirements of the IFRS16 standard represented in the requirements for proving lease contracts, the requirements for measuring them, and the requirements for presenting and disclosing them in the financial statements in the Algerian environment will have a fundamental effect on the content of the financial statements and the quality of accounting information, as well as the various decisions taken by the users of the financial statements. Therefore, this effect is related to the extent to which the Algerian economic institutions are able to control and comply with the application of the requirements of the IFRS16 standard related to lease contracts. The current research work recommended the necessity to update the rules of the financial accounting system SCF and to make the necessary amendments to the fiscal legislation in line with the new requirements of the IFRS16 standard and to provide an appropriate environment that permits an effective implementation of these requirements by Algerian economic institutions.
IFRS 16 المتعلق بعقود الإيجار على القوائم المالية المعدة وفق النظام المحاسبي المالي في الجزائر - دراسة ميدانية
أطروحة
Keywords: معيار الدولي للإبلاغ المالي IFRS16; عقود الإيجار; قوائم مالية; حق استخدام الأصل; التزام الإيجار; International Financial Reporting Standard IFRS16; Lease contracts; Financial statements; Right of Use Asset; Lease liabilities.